ROLE OF INDIAN CULTURE AND TRADITIONS IN THE SUSTAINABLE PRACTICES THROUGH ART EDUCATION - Bhosale, Neelam; Mallik, Ranjan Kumar; Singh, Arjun Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sustainability refers to the practice of conserving natural resources and preventing their exhaustion, hence ensuring the maintenance of an ecological equilibrium. Sustainable development and this notion are intimately interconnected, yet they are sometimes mistaken for one another. For many years, people have been engaging in discussions about the concept of a ’sustainable lifestyle’ and ’sustainable development,’ but have failed to incorporate it into their daily lives. The occurrence of this adaptation is contingent upon our ability to cultivate the practice of sustainable living within our households. Subjects such as Art may provide insights into environmental conservation and promote the use of practices like reusing, recycling, and upcycling materials for artistic endeavors. This study examines the relationship between Art and Design, specifically focusing on how it promotes awareness and facilitates the adoption of sustainable living practices. This project utilizes art-based action research to foster the development of worldwide, transdisciplinary, and culturally sustainable Art Education. Its aim is to transform the mindset of the general public towards sustainable practices. The research used the four-field paradigm to emphasize the diverse and complex function of Indian folk art in both individual and collective artistic pursuits.